2014
DOI: 10.1063/1.4902513
|View full text |Cite
|
Sign up to set email alerts
|

Phase-coherent electron transport in (Zn, Al)Ox thin films grown by atomic layer deposition

Abstract: A clear signature of disorder induced quantum-interference phenomena leading to phase-coherent electron transport was observed in (Zn, Al)Ox thin films grown by atomic layer deposition. The degree of static-disorder was tuned by varying the Al concentration through periodic incorporation of Al2O3 sub-monolayer in ZnO. All the films showed small negative magnetoresistance due to magnetic field suppressed weak-localization effect. The temperature dependence of phase-coherence length (lφ∝T−3/4), as extracted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…Negative MR in TCO is often observed in the weak localization regime. Furthermore, such cases are usually observed at low temperatures [15,24]. An understanding of the experimental data based on the WL model requires the existence of extended states at low temperatures.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Negative MR in TCO is often observed in the weak localization regime. Furthermore, such cases are usually observed at low temperatures [15,24]. An understanding of the experimental data based on the WL model requires the existence of extended states at low temperatures.…”
Section: Methodsmentioning
confidence: 98%
“…For example, it was shown that pure and Cu doped ZnO films have a negative magnetoresistance [14]. Al doped ZnO films grown by atomic layer deposition also had a negative magnetoresistance [15]. Other thin TCO films such as indium tin oxide [16][17][18], B-doped ZnO [19], phosphorus-doped ZnO [20] and tin oxide [21,22] demonstrated a similar dependence of magnetoresistance on a magnetic field.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In such delta‐doped semiconductors, 2D electron gases (2DEGs) are formed at the interfaces which are localized within a “V” shape potential well formed by the ionized impurity potentials of the dopants . However, in the present case, formation of such vertically stacked multiple 2DEGs is quite impossible because of the degenerate nature of the ZnO spacer layer . This could be explained by considering the effective screening of Al impurity potentials by the free electrons in the sufficiently thick ( l > l c ) ZnO spacer layers .…”
Section: Resultsmentioning
confidence: 87%
“…In a recent report, Lee et al have proposed an “effective field model” of extrinsic doping to interpret the room temperature electrical properties of ALD‐grown Al‐doped ZnO (AZO) films. However, in the present comment, we want to emphasize that such model of extrinsic doping is misleading as the measured carrier density for all the AZO films including the host ZnO is higher than the Mott critical density ( n c = 1 × 10 19 cm −3 ) required for the insulator‐to‐metal transition . While constructing the doping model, the authors have considered only the effect of dielectric screening of the ionized Al impurities by taking into account the static dielectric constant of ZnO in the expression for the effective Bohr orbital radius (Equation 4 in ref.…”
Section: Introductionmentioning
confidence: 99%